Perinatal conditions and early assessment of low-birth-weight premature infants - Louthrenoo O. (2014)
The developmental assessment of 60 low-birth-weight premature infants, who had no major handicap, was compared with that of 30 term infants at a chronological age of 6 months. Both groups showed no statistically significant differences in mean scores for the Bayley Scales of Infant Development, but the premature group was more likely to have a clinically significant lower function. The premature infants' mental performance had a significantly inverse correlation with the number of days spent in hospital. Follow-up was essential for this group of children in obtaining the early detection of any handicap and performing timely therapeutic intervention.